Effects of local vibration combined with extracorporeal shock wave therapy in plantar fasciitis: a randomized controlled trial - HyoJeong On; JongEun Yim (Journal of Rehabilitation Medicine, 2023)
Objective:To compare the effects of local vibration combined with extracorporeal shock wave therapy and extracorporeal shock wave therapy alone for plantar fasciitis.